Anoxic Iron Cycling Bacteria from an Iron Sulfide- and Nitrate-Rich Freshwater Environment - Haaijer, Suzanne C.; Crienen, Gijs; Jetten, Mike S.; Op den Camp, Huub J. (Frontiers in Microbiology, 2012)
In this study, both culture-dependent and culture-independent methods were used to determine whether the iron sulfide mineral- and nitrate-rich freshwater nature reserve Het Zwart Water accommodates anoxic microbial iron cycling. Molecular analyses (16S rRNA gene clone library and FISH) showed that sulfur-oxidizing denitrifiers dominated the microbial population. In addition, bacteria resembling the iron-oxidizing, nitrate-reducing Acidovorax strain BrG1 accounted for a major part of the microbial community in the groundwater of this ecosystem. Despite the apparent abundance of strain BrG1-like bacteria, iron-oxidizing nitrate reducers could not be isolated, likely due to the strictly autotrophic cultivation conditions adopted in our study. In contrast an iron-reducing Geobacter sp. was isolated from this environment while FISH and 16S rRNA gene clone library analyses did not reveal any Geobacter sp.-related sequences in the groundwater. Our findings indicate that iron-oxidizing nitrate reducers may be of importance to the redox cycling of iron in the groundwater of our study site and illustrate the necessity of employing both culture-dependent and independent methods in studies on microbial processes.